The relationship between carotid intima-media thickness and carotid plaque in the Northern Manhattan Study. Issue 2 (August 2015) - Rundek, Tatjana; Gardener, Hannah; Della-Morte, David; Dong, Chuanhui; Cabral, Digna; Tiozzo, Eduardo; Roberts, Eugene; Crisby, Milita; Cheung, Kuen; Demmer, Ryan; Elkind, Mitchell S.V.; Sacco, Ralph L.; et al.
Abstract: Objective: Carotid intima-media thickness (cIMT) and carotid plaque (CP) are proposed biomarkers of subclinical atherosclerosis associated with stroke risk. Whether cIMT and CP are distinct phenotypes or single traits at different stages of atherosclerotic development is unclear. We explored the relationship between these markers in the population-based Northern Manhattan Study. Methods: We used high-resolution ultrasound and validated imaging protocols to study the cross-sectional (N = 1788 stroke-free participants) and prospective relationship (N = 768 with follow-up scan; mean years between examinations = 3.5) between CP and cIMT measured in plaque-free areas. Results: The mean age was 66 ± 9 (40% male, 19% black, 17% white, 61% Hispanic). The mean baseline cIMT was 0.92 ± 0.09 mm, 0.94 ± 0.09 mm among the 58% with prevalent plaque, 0.90 ± 0.08 mm among the 42% without prevalent plaque (p < 0.0001). Each 0.1 mm increase in baseline cIMT was associated with a 1.72-fold increased odds of plaque presence (95%CI = 1.50–1.97), increased plaque thickness (effect on the median = 0.46 mm, p < 0.0001), and increased plaque area (effect on the median = 3.45 mm 2, p < 0.0001), adjusting for demographics and vascular risk factors. Elevated baseline cIMT was associated with an increased risk of new plaque in any location at follow-up, but after adjusting for demographics and vascular risk factors this association was no longer present. No association was observed in carotid segment-specific analyses. Conclusion: Increased cIMT was associated with baseline prevalent plaque but did not predict incident plaque independent of other vascular risk factors. This finding suggests that increased cIMT is not an independent predictor of plaque development although these atherosclerotic phenotypes often coexist and share some common vascular determinants.